A protocol for developing a core outcome set for ectopic pregnancy - Krystle Y. Chong (BMC, 2021)
Abstract Background Randomised controlled trials (RCTs) evaluating ectopic pregnancy have reported many different outcomes, which are themselves often defined and measured in distinct ways. This level of variation results in an inability to compare results of individual RCTs. The development of a core outcome set to ensure outcomes important to key stakeholders are collected consistently will guide future research in ectopic pregnancy. Study aim To develop and implement a core outcome set to guide future research in ectopic pregnancy. Methods and analysis We have established an international steering group of key stakeholders, including healthcare professionals, researchers, and individuals with lived experience of ectopic pregnancy. We will identify potential outcomes from ectopic pregnancy from a comprehensive literature review of published randomised controlled trials. We will then utilise a modified Delphi method to prioritise outcomes. Subsequently, key stakeholders will be invited to score potential core outcomes on a nine-point Likert scale, ranging from 1 (not important) to 9 (critical). Repeated reflection and rescoring should promote whole and individual stakeholder group convergence towards consensus ‘core’ outcomes. We will also establish standardised definitions and recommend high-quality measurements for individual core outcomes. Trial registration COMET 1492 . Registered in November 2019.